Interpretasi Makna pada Album Lagu “Kalah Bertaruh” Karya Nadin Amizah dalam Kajian Semiotika - Fajrin, Rahmawati; Idris, Idris; Idris, Muhammad (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2025)
This study aims to examine the form and meaning of symbols in Nadin Amizah's album "Kalah Bertaruh" using Ferdinand de Saussure's semiotic approach. The research focuses on three main songs: "As Our Destiny Is Written," "Crying on the Way Home," and "Finish." The method used is descriptive qualitative with content analysis. The analysis is carried out by identifying linguistic sign units in the lyrics, classifying denotative and connotative meanings, and relating them to the visual context of the music video. Primary data is obtained from the song lyrics and supporting data comes from Nadin Amizah's digital footprint through social media platforms. The results show that the signs in the song lyrics form meaning through the relationship between the signifier and the signified, such as symbols of sadness, the strength to let go, and the courage to face reality. In addition, the visual elements in the music video also enrich the interpretation of meaning. These findings prove that musical works can be a powerful medium of expression and communication, and demonstrate how semiotics can be applied in analyzing modern artwork.